2010
DOI: 10.1111/j.1475-4754.2009.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Applicability of Conventional Methods for the Chemical Characterization of Waterlogged Archaeological Wood

Abstract: A series of 112 waterlogged archaeological wood samples of different provenances, wood species, burial times and states of preservation were analysed with the aim of assessing the validity (in terms of limits and reliability) of procedures conventionally used in the pulp and paper industry, to evaluate the state of preservation of decayed wood. In particular, the extent of any damage wrought on decayed wood tissue by the repetitive cycles that characterize these procedures was evaluated as a function of the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Holocellulose content was calculated as 100% minus the arithmetic sum of the other chemical components, since it was previously shown that the direct assessment of holocellulose content gave values with a low accuracy in archaeological material [26].…”
Section: Wet Chemical Analysesmentioning
confidence: 99%
“…Holocellulose content was calculated as 100% minus the arithmetic sum of the other chemical components, since it was previously shown that the direct assessment of holocellulose content gave values with a low accuracy in archaeological material [26].…”
Section: Wet Chemical Analysesmentioning
confidence: 99%
“…In fact, it has previously been shown that direct measurement of the holocellulose content, instead of its calculation, is unreliable in archaeological material (Pizzo et al . ). The ash content, following the procedure described in TAPPI standard T211, which involves the air calcination of wood samples at 550°C.…”
Section: Methodsmentioning
confidence: 97%
“…In the present case, the chemical characterization was performed at two levels: when samples were large enough to have an appreciable amount of useful material, it was carried out through conventional and reliable methods, such as wet chemical analyses, as specifically described in Pizzo et al . ; on almost all the samples, both small and more abundant, analyses were performed by means of attenuated total reflectance Fourier transform – infrared (ATR‐FT–IR) spectroscopy, according to the methodology described in Pizzo et al . ().…”
Section: Methodsmentioning
confidence: 99%
“…Softwood and hardwood can be identified from their characteristic lignin components, and the content of lignin (Klason lignin structure) can be determined. 10,32 The degree of deterioration can be estimated from the relative amounts of cellulose, hemicellulose and lignin, which display characteristic infrared absorption bands in "fingerprint" wavenumber regions from about 1800 to 800 cm -1 . Many reports describe qualitative changes in FT-IR spectra related to decay of wood over long periods of exposure.…”
Section: ·2 Fourier-transform Infrared (Ft-ir) Spectroscopymentioning
confidence: 99%